Posisi Wanita dalam Sistem Politik Islam Perspektif Fenomelogi - Abdul Hadi (An Nisa'a, 2017)
Islam does not know discrimination between woman and men. Islam placed woman as parallel partner of men. Even so there is difference, hence that is effect of especial duties and function burdened by religion to each gender, so that the existing difference do not result which is one sense of belonging of excess for other. Both each other equip and assist to assist in playing the part of its function in life and the life. This article means to study how to domicile woman from political dimension Islam system.